Investigating potential sources of sore throat: physico-chemical attributes and microbial contamination in rambutan from fresh harvests and retail stores - Iliya Zakirah Izhar,; Saiful Irwan Zubairi,; Zainun Nurzahim,; Harisun Yaakob,; Zalifah Mohd Kasim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Rambutan (Nephelium lappaceum), a tropical fruit cherished for its succulent flesh and vibrant appearance, is cultivated extensively across various regions worldwide. However, despite its popularity, the fruit faces challenges related to particulate contamination during the harvesting process. Particulate matter contamination refers to the presence of solid or liquid particles suspended in the air or adhered to the fruit’s surface, posing potential risks to both consumer health and fruit quality. Hence, this study aims to identify the factors in rambutan that could cause sore throats by analysing its physicochemical properties and conducting a microbiological study. For this study, two samples of rambutan fruit which are rambutan sold in stores (RS) and rambutan freshly harvested from the tree (RT) were collected and analysed for their external peel, internal peel, and pulp parts (n = 3). The assessment included the weight of visible fine dirt, pH value, oil content, surface morphology and total coliform (TPC). The results showed that the weight of visible fine dirt on RT external peel (93.50 ± 5.00 mg) and the pH value of its external peel and pulp (4.17 ± 0.00 - 5.17 ± 0.00) were significantly higher and more acidic (p<0.05) than those of RS. However, there were insignificant differences (P<0.05) in oil content (0.36 ± 0.7 - 0.38 ± 0.8%) between the external peels of the rambutan samples. Additionally, the surface morphology and image analysis of RS showed more foreign particles, represented as black or white dots on its internal peel and pulp, compared to RT, which was suspected to be yeast. Moreover, the total coliform count for both samples was significantly different (p<0.05) in their external peel and pulp, but it was still within the safe eating limit. The study concluded that environmental pollution and contamination during rambutan handling could cause sore throat.